Sosialisasi Digital Marketing dan Pembuatan Maps guna Meningkatkan Daya Saing UMKM di Kelurahan Toapaya Asri - Anita Rahayu; Disti Apriani; Elina Bayusri; Erma Yani; Eva Fitri; Heppi Naomi Lastio Sihombing; Irmawati; Rachel Andrea; Rapita Purba; Wama Wati; Annissa Valentina (JURPIKAT, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Toapaya Asri Village face challenges in utilizing digital technology for product marketing. The main issue is low digital literacy, which causes MSMEs to rely solely on conventional marketing. This community service aims to increase the competitiveness of MSMEs through education and digital marketing assistance. The method used is the Community Empowerment System (Sisdamas) through socialization and practical assistance. As a result, 34 MSME actors gained an understanding of digital marketing strategies, product packaging, and labeling. MSME actors also successfully created Google Maps accounts and added their business locations, increasing visibility and market reach. This community service contributed significantly to strengthening the local economy through increased digital literacy and the sustainable competitiveness of MSMEs.